Zagrożenia dla Polski w obliczu presji migracyjnej ze wschodu - Andrzej Zapałowski (Przegląd Geopolityczny)
The purpose of the article is to explain the mechanism of forced migration and its impact on the security of the invaded state, using contemporary Poland as an example. In order to introduce the phenomenon of coercive engineered migration, the author cites historical examples of its use by the authorities of totalitarian states, especially the Soviet Union. The main part of the article is devoted to the analysis of various forms of threats to Poland's security generated by Russia and Belarus, and the possibility of escalation of these threats. The analysis of the geopolitical situation shows that the biggest threat to Poland is the migratory pressure caused by the wars in the Middle East, and on the other hand by the creation of a new migration route through the territory of Ukraine. The author was critical of the level of threat recognition, also pointing out the limited possibilities of counteracting both migratory pressure and unfavorable processes on the territory of Ukraine, which will be a consequence of the reduction of aid from the West to this country, as well as the escalation of conflicts in the Islamic region.